Sistem Informasi Administrasi Skripsi Pada Program Studi Peternakan di Universitas Kristen Wira Wacana Sumba Berbasis Website - Ferderika Nathan Tawa; Fajar Hariadi; Raynesta Mikaela Indri Malo (STIKes Ibnu Sina Ajibarang, 2024)
Thesis at the Wira Wacana Christian University Sumba Animal Husbandry Study Program involves the stages of submitting a title, registering for a proposal exam, and a thesis exam. This process currently uses Google Forms, with result announcements via WhatsApp, creating inconsistencies and taking a long time. Changing the thesis title requires additional steps, such as students having to come to campus to remove the old title after it is rejected. Challenges also arise in tracking the frequency of tutoring, especially with large student numbers. This research aims to develop an effective solution by applying the Extreme Programming (XP) method in developing web-based applications. Based on the System Usability Scale (SUS) test, this application received a usability score of 80.2%, making it suitable for use. The successful implementation of this web application makes a positive contribution in improving the quality and efficiency of thesis management in the Wira Wacana Christian University Sumba Animal Husbandry Study Program.